Giant Fibrovascular Polyp of the Esophagus: A Novel Technical Approach - Juan José Trakál; Guillermo Jorge Sarquis; Juan Antonio Muñoz; Sergio Barril; Esteban Trakál; Lucas Armando; Rosa Carolina Gorordo Ipiña (Case Reports in Gastrointestinal Medicine)
Fibrovascular polyps (FVPs) of the esophagus are rare, and their course is usually indolent until reaching enormous proportions. It is a dramatic entity owing to its tendency to cause bizarre complications. We describe a 49-year-old female patient with sudden dyspnoea that required digital maneuvers to clear the airway. After diagnosing, an FVP of the esophagus, a video-assisted endocavitary surgery was made. Histopathological examination revealed a fibrovascular polyp. Endoscopic controls after excision show no mass or symptoms recurrence.